Sustainable housing for the elderly - Kerbler, Boštjan (Journal for Geography, 2011)
Developed countries are facing increased financial demands in providing appropriate social and health care due to the ageing of the population and in addition to the issues of insufficient capacities and long waiting lists at hospitals and retirement homes. Countries’ financial capacities to ensure the current level and extent of health and social care services are decreasing, also due to economic uncertainty and the increasingly greater share of the nonworking population. For that reason demands are raising for more sustainable ways of housing and services for the elderly. The article starts from the assumption that the idea could be achieved by reorganising of housing units and relocation of care services into the home environment of older people, and thereby make it possible for the elderly to remain in their home environments as long as possible, capable of living as independently as possible with high quality of life.
Keywords: ageing population; elderly people; sustainable housing; remote home care; telecare